PENGARUH AERASI LARUTAN FeDTA DAN PAKAN TAMBAHAN TEPUNG Spirulina maxima TERHADAP JUMLAH KISTA YANG DIHASILKAN OLEH Artemia salina BETINA OVIPAR - M. Noor (Jurnal Perikanan Universitas Gadjah Mada, 2002)
Different media condition, with salinity above the hatching threshold of cysts (100 ppt) and feeding with water flow as the main menu and Spirulina maxima flour as an additional feed encouraged the adult female Artemia salina to be oviparous and produce different amount of cysts depending on the treatments. The average amount of cysts produced by oviparous female Artemia salina during 77 day rearing was 22,719-78,616 cysts each female Artemia salina produced 18-13 cysts. Statistical analysis showed that all treatments did not reduce any significant effects on the production of cysts (p>0.05)